Identification of the awareness level by the public of Arab countries toward COVID-19: cross-sectional study following an outbreak - Ruwidah Bonyan; Aseel Fuad Al-Karasneh; Faris El-Dahiyat; Ammar Abdulrahman Jairoun (Taylor & Francis Group, 2020)
Background The novel coronavirus disease 2019 (COVID-19) pandemic is a global challenge. Improving public awareness about preventive measures and disseminating appropriate information about COVID-19 has a critical role in containing the disease. Aim To evaluate and determine the factors that may affect the level of awareness and responses toward COVID-19 in Arab countries. The study could be helpful in identifying where more public education about COVID-19 is needed. Method This cross-sectional, online descriptive questionnaire-based study was conducted in February and March 2020. A total of 485 participants from Arabic-speaking countries (Jordan, United Arab Emirates, the Kingdom of Saudi Arabia, Qatar, Palestine, and Egypt) were asked to complete this Arabic-translated survey using social media platforms (Facebook and WhatsApp). Result In general, there was a good level of awareness of the participants regarding COVID-19. Higher awareness scores were significantly correlated with older participants [odds ratio (OR) 1.019; 95% CI 1.012-1.026], those who attended awareness campaigns [OR 1.212; 95% CI 1.081-1.358], secondary school education holders [OR 1.740; 95% CI 1.096-2.763], higher education diploma holders [OR 2.090; 95% CI 1.297-3.368], university degree holders [OR 1.969; 95% CI 1.265-3.066], those who have post-graduate education [OR 2.206; 95% CI 1.393-3.493], and healthcare employees [OR 1.259; 95% CI 1.025-1.547]. Conclusions The COVID-19 pandemic is causing global panic; thus, awareness and practices of preventive measures of COVID-19 should be increased through public educational campaigns, which should be planned in accordance with communities' and countries' attitudes toward COVID-19. Collaborative efforts between ministries of heath and residents of every country should be implemented.